Cleaning and modification of intraorally contaminated titanium discs with calcium phosphate powder abrasive treatment. Issue 11 (8th August 2012) - Tastepe, Ceylin S.; Liu, Yuelian; Visscher, Corine M.; Wismeijer, Daniel
Abstract Objective The aim of this study was to evaluate the cleaning efficiency on intraorally contaminated titanium discs by using calcium phosphate and air powder abrasive (APA) treatment. The modification of titanium surface (SLA) was evaluated and compared with the conventional air powder abrasive methods and phosphoric acid. This treatment modality might give new perspectives for peri‐implant surface treatment. Materials and Methods A total of 36 SLA surface titanium discs were kept in the human mouth for 48 h by 14 volunteers. The intraorally contaminated discs were stained with erythrosine dye to make the biofilm visible. Discs were randomly assigned to one of the six groups: APA without powder‐only water and air (Control). APA with Hydroxylapatite (HA). APA with Hydroxylapatite and Calcium Phosphate (HA + TCP). APA with Titanium Dioxide (TiO2). APA with EMS Soft Subgingival powder (EMS). Phosphoric Acid. Light microscope photos were taken during the treatment. Following the cleaning, the residual biofilm, surface changes, and surface chemical content were evaluated using Scanning Electron Microscopy (SEM) and Energy Dispersive X‐Ray Spectroscopy (EDS). A systematic random sampling protocol and a point counting method were applied for the quantitative evaluation of the remaining biofilm. Multiple comparisons within and between groups are performed by Kruskall Wallis test and if significant Mann–Whitney U‐test as post hoc testing is applied. The significance level was P < 0.05. Results All methods with the exception of phosphoric acid could decrease the initial amount of biofilm significantly. Among all air powder abrasive treatments, the HA + TCP group showed the best results with 99% biofilm removal, followed by HA and EMS powders. The cleaning method caused minimal changes to the surface structure. With the exception of the control group, all air powder applications caused sharp edges around the grooves in the implant surface to be rounded. TiO2 powder caused less change than HA and HA + TCP. Phosphoric acid did not cause a visible surface change on the SEM photos. Powder particles remnants were observed on and impacted in the titanium surface. In the HA and HA + TCP group, a Ca content was observed varying between 2% and 5%. In the control group, saliva and biofilm‐related elements were observed. Conclusions Using the air powder abrasive method with calcium phosphate powders on contaminated titanium discs, an efficient implant cleaning and surface modification can be achieved. This method should be further improved as it has possible potential to be used as an implant surface treatment method for implants involved with peri‐implantitis.